SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SEPEDA MOTOR BEKAS MENGGUNAKAN METODE WASPAS - Heru Sugara (Politeknik Bisnis Indonesia, 2022)
This study aims to solve the problem of selecting second-hand motorcycle purchases from the general public by CV. Asli Pematangsiantar Motor. Asli Motor Pematangsiantar is a second-hand motorcycle dealer that accepts purchases from the public. In assessing the price and quality of used motorbikes offered by the public to the Asli Motor Pematangsiantar dealers, this company still uses methods based on unmeasured appraisals, resulting in a lack of standard certainty in choosing to buy used motorcycle from the public. To solve this problem, a Decision Support System was designed that can be used as a tool in determining which motorbikes are worth buying from the public. The Decision Support System used to solve this problem uses the Weighted Aggregated Sum Product Assessment (WASPAS) method. The criteria used in this DSS consist of the year of the vehicle, the advantages and disadvantages of the vehicle, the completeness of the documents and the bid price. The results of data processing using WASPAS method consist of alternatives with the greatest value A007 with a final result of 38.9583. With the application using WASPAS method, the selection of the best vehicles offered by sellers to Asli Motor dealers can be carried out effectively and efficiently.